2005
DOI: 10.2337/diacare.28.8.1882
|View full text |Cite
|
Sign up to set email alerts
|

Family History of Type 2 Diabetes Is Associated With Increased Carotid Artery Intimal-Medial Thickness in Mexican Americans

Abstract: OBJECTIVE -To evaluate whether the joint risk of diabetes and atherosclerosis tracked within families, we assessed the correlation between a family history of diabetes and intimalmedial thickness (IMT) of the common carotid artery (CCA).RESEARCH DESIGN AND METHODS -Study subjects included 620 nondiabetic individuals from 24 families enrolled in the San Antonio Family Heart Study. The thickness of the far walls of the CCA was measured by B-mode ultrasonography. Statistical analyses included familial correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
2
19
1
Order By: Relevance
“…The small number of studied individuals did not allow a separate evaluation by sex, but that does not limit the importance of the study, since it meets Boissel's three criteria for surrogacy (efficiency and convenience, as a noninvasive method; linkage; and congruency). The advantages of the method range from a lower sample number to the confirmation of a direct association between the measurements and the disease process 8,30 . It is known that ultrasonography does not allow for differentiation between an intimal atherosclerotic process and medial hypertrophy, due to arterial blood pressure effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small number of studied individuals did not allow a separate evaluation by sex, but that does not limit the importance of the study, since it meets Boissel's three criteria for surrogacy (efficiency and convenience, as a noninvasive method; linkage; and congruency). The advantages of the method range from a lower sample number to the confirmation of a direct association between the measurements and the disease process 8,30 . It is known that ultrasonography does not allow for differentiation between an intimal atherosclerotic process and medial hypertrophy, due to arterial blood pressure effects.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography is a valuable and practical tool for the study of the early evolution of atherosclerosis, transforming us from mere spectators into active inducers of a regression of the atherosclerotic process, even before its first clinical manifestations 30 . It is a proposed cardiovascular risk marker to estimate coronary heart disease susceptibility, since no existing risk score 26 includes altogether obesity, a positive family history of premature coronary heart disease, a family history of diabetes mellitus, sedentary life and/or psychological and economical factors, among others, focusing only on fatal and non-fatal coronary disease, but not ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38] Because diabetes and CVD share risk factors such as obesity and dyslipidemia and might even share etiology, 39,40 people with a family history of diabetes show increased risk for CVD. [41][42][43][44] Conversely, people with a family history of CVD might show early signs of insulin resistance and impaired glucose metabolism and, ultimately, risk of diabetes. [45][46][47] This sharing of risk factors, and possibly of etiology, has important implications regarding joint screening and prevention strategies for the 2 diseases.…”
Section: Family History As An Independent Risk Factor For Type 2 Diabmentioning
confidence: 99%
“…While several studies (10 -12) have shown that a family history of diabetes can increase cardiovascular risk, including subclinical atherosclerosis (11), no study has examined the converse, which is that familial risk of coronary heart disease (CHD) could influence the risk of type 2 diabetes. To test this hypothesis, we measured the association between the familial risk of CHD using the CHD family risk score (CHD-FRS) and incident type 2 diabetes in the Atherosclerosis Risk in Communities (ARIC) study.…”
mentioning
confidence: 99%